2016
DOI: 10.1016/j.envpol.2016.03.067
|View full text |Cite
|
Sign up to set email alerts
|

Environment and gut morphology influence microplastic retention in langoustine, Nephrops norvegicus

Abstract: Over the past twenty years microplastic pollution has been recorded in all major marine habitats, and is now considered to be of high environmental concern. Correspondingly, the number of reports of microplastic ingestion by marine species is increasing. Despite this, there are still relatively few studies which address the uptake and retention of microplastic in wild populations. Langoustine, Nephrops norvegicus, sampled from the Clyde Sea Area, have previously been seen to contain large aggregations of micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(117 citation statements)
references
References 44 publications
5
110
1
1
Order By: Relevance
“…More recently, Welden found that polyethylene, polypropylene, and nylon rope in subtidal conditions (10 m depth) of the Clyde Sea area (Scotland) exhibited a reduction in weight, averaging between 0.39% and 1.02% per month, and suggested that this weight loss was the result of the release of microplastic particles. Of interest is that Welden found no correlation between the reduction in mechanical properties and the reduction in weight of the ropes. This finding suggests that microplastic particles may be produced from degrading plastic material before a significant reduction in mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Welden found that polyethylene, polypropylene, and nylon rope in subtidal conditions (10 m depth) of the Clyde Sea area (Scotland) exhibited a reduction in weight, averaging between 0.39% and 1.02% per month, and suggested that this weight loss was the result of the release of microplastic particles. Of interest is that Welden found no correlation between the reduction in mechanical properties and the reduction in weight of the ropes. This finding suggests that microplastic particles may be produced from degrading plastic material before a significant reduction in mechanical properties.…”
Section: Discussionmentioning
confidence: 99%
“…In both studies, MPs (predominantly fibers) were detected in 63% [51] and 83% [52] of the examined animals. A recent study by Welden and Cowie [1] with N. norvegicus confirmed that MP exposure negatively affects feeding, body mass, metabolic activity, and energy reserves. An 8-month exposure to PP fibers via food (0.2-5 mm, five fibers per feeding) resulted in formations of MP aggregates in the gut of the langoustine that might have reduced the uptake of nutrients.…”
Section: Other Crustaceansmentioning
confidence: 98%
“…Yet, marine research has shown malnutrition caused by the intensive feeding on MPs replacing parts of the natural diet [1][2][3]. Additionally, further ingestion-related effects include blockages and injuries to the digestive tract [4], inflammatory response [5], and desorption of xenobiotics [6].…”
Section: à3mentioning
confidence: 99%
“…Statistical analysis of the results was carried out as outlined in Welden and Cowie (2016a). Data were analysed using 145 R Studio version 1.0.44.…”
Section: Statistical Analysis 144mentioning
confidence: 99%
“…The 51 tendency for crustaceans to take in plastic is supported by a number of observations in wild caught animals. Whilst 52 the number of studies is comparatively low, the uptake of microplastics in wild crustaceans has been seen to be 53 highly heterogeneous, varying with location (Devriese et al, 2015;Welden and Cowie, 2016a). This may be partially 54 due to variation in environmental levels of microplastic, however, retention in Nephrops norvegicus has also been 55 linked to size, sex and moult stage (Welden and Cowie, 2016a).…”
Section: Introduction 38mentioning
confidence: 99%